A combination of polak-ribiere and hestenes-steifel coefficient in conjugate gradient method for unconstrained optimization - Mustafa, Mamat; Mohd, Rivaie; Nurul Hajar, Mohd Yussoff (HIKARI Ltd., 2015)
One of popular methods in solving unconstrained optimization method is conjugate gradient methods (CG). This paper presents a new CG method based on combination of two classical CG methods. Global convergence properties play the important part in CG methods. Numerical result show that this new CG method is quite effective when measured based on number of iteration and CPU times.